2014
DOI: 10.1002/ana.24066
|View full text |Cite
|
Sign up to set email alerts
|

Lewy body extracts from Parkinson disease brains trigger α‐synuclein pathology and neurodegeneration in mice and monkeys

Abstract: α-Synuclein species contained in PD-derived LB are pathogenic and have the capacity to initiate a PD-like pathological process, including intracellular and presynaptic accumulations of pathological α-synuclein in different brain areas and slowly progressive axon-initiated dopaminergic nigrostriatal neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
511
6
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(575 citation statements)
references
References 43 publications
32
511
6
9
Order By: Relevance
“…Subsequently, in vitro and in vivo studies confirmed the ability of aSyn to be released/secreted and taken up by neighboring cells (18)(19)(20), further supporting the prion-like spreading of aSyn.…”
Section: Significancementioning
confidence: 74%
See 1 more Smart Citation
“…Subsequently, in vitro and in vivo studies confirmed the ability of aSyn to be released/secreted and taken up by neighboring cells (18)(19)(20), further supporting the prion-like spreading of aSyn.…”
Section: Significancementioning
confidence: 74%
“…Because the application of The assignments are represented in percentage and were attributed to each peak observed according to Susi and Byler (75). pathological aSyn species has been reported to induce a glial response in vivo (20,36), we investigated the state of the astrocytes by probing for glial fibrillary acidic protein (GFAP). An increase in GFAP levels could only be detected in cells exposed to WT -Cu 2+ and H50Q -Cu 2+ , likely because of the development of reactive astrocytes, as GFAP staining revealed a phenotype compatible with reactive astrocytes (37) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our ability to now synchronously and rapidly induce a motor phenotype and αS pathology by a peripheral injection of αS may prove invaluable in future studies exploring mechanisms of pathology induction and αS toxicity and may extend recent studies showing rapid induction following intracerebral inoculation (21)(22)(23)(24)(25)(26). Our finding that disease onset in M83 Tg mice can be shortened, predicted, and synchronized through a simple manipulation provides a valuable model to accelerate studies designed to fully understand the mechanisms underlying induction of the inclusion pathology and motor phenotype, but also to enable much more rapid and cost-effective preclinical testing of novel PD therapies.…”
Section: Discussionmentioning
confidence: 96%
“…And it has been suggested that αS pathology might originate in the nerves of the PNS and spread to the CNS (14). Experimentally, it has been reported that intracerebral injections of preformed amyloidogenic αS fibrils in nontransgenic (nTg) and αS transgenic (Tg) mice induce the formation of intracellular αS inclusions that appear to progress from the site of injection (21)(22)(23)(24)(25)(26). Collectively, these studies support the notion that αS inclusion pathology may propagate via a prion-like conformational self-templating mechanism (27,28).…”
mentioning
confidence: 99%
“…The next step was to move from mice to non human primates. In 2014, a team at the University of Barcelona in Spain injected Lewy bodies extracted from human brains into the substantia nigra and striatum of four macaque monkeys 8 . Over 14 months the researchers observed gradual neuronal degeneration, first of the long axons that extend from neurons in the substantia nigra to the striatum, then of the substantia nigra neurons themselves.…”
Section: Pursuing Proofmentioning
confidence: 99%